Oxidative stress in rats experimentally infected by Sporothrix schenckii - Castro V.S.P. (2017)
© 2017 Elsevier LtdThe aim of this study was to evaluate whether oxidative stress occurs in rats experimentally infected by Sporothrix schenckii, and its possible effect on disease pathogenesis. Thirty rats were divided into two groups: the group A (uninfected, n = 18) and the group B (infected by S. schenckii, n=21). Blood samples were collected on days 15, 30 and 40 post-infection (PI). At each sampling time, six rats of the group A, and seven of the group B were bled. TBARS (thiobarbituric acid reactive substances) levels in serum samples were measured to evaluate lipid peroxidation. In addition, catalase (CAT) and superoxide dismutase (SOD) activities, known as biomarkers of antioxidants levels, were verified in whole blood. Seric pro-inflammatory cytokine levels were measured (IFN-γ, TNF-α, and IL-6), which showed that these inflammatory mediators were at higher levels in the infected rats (P < 0.001). In comparison to uninfected animals, rats with sporotrichosis showed significantly higher (p < 0.01) levels of TBARS on day 40 PI; CAT activity was significantly increased (p < 0.01) on days 30 and 40 PI; and SOD activity was increased (p < 0.01) on day 40 PI. Infected rats showed larger testicles and granulomas in the testicular capsule, as well as hepatic granulomas and splenic follicular hyperplasia. All tissues (testicle, spleen, and liver) showed inflammation associated with numerous fungal structures. These results demonstrated that the intense inflammatory response (seric and tissue) in sporotrichosis is a likely mechanism for redox imbalance, and consequently cause the oxidative stress in experimentally infected rats.